Graphene Oxide Film As A Passive Q-Switcher In An Erbium-Doped Fiber Laser Cavity - Che Mat, Fauziah; Yasin, Moh; Abdul Latiff, Anas; Harun, Sulaiman Wadi (Photonics Society Of Poland, 2017)
All-fiber passively Q-switched fiber lasers have been demonstrated by using a graphene oxide (GO) Q-switcher for possible applications in telecommunication, laser processing, fiber sensing and medicine. The GO material was obtained through a modified Hummers method from expanded acid washed graphite flakes and was embedded into a polyvinyl alcohol (PVA) film to form a saturable absorber (SA) device. The Q-switched pulse operates at 1563.3nm with a repetition rate that can be tuned from 44.33kHz to 61.77kHz as the pump power changes from 39mW to 96mW. The highest repetition rate of 61.77kHz is achieved at a pump power of 96mW and it is observed that the Q-switched pulse produced a maximum pulse energy of 0.054nJ and pulse width of 5.57μs at 96mW pump power.